2019
DOI: 10.32553/ijmbs.v3i8.492
|View full text |Cite
|
Sign up to set email alerts
|

The THE ROLE OF PROBIOTIC SUPPLEMENTATION ON THE IMMUNE SYSTEM IN ELDERLY

Abstract: Elderly tends to be more susceptible to infections and chronic diseases. Malnutrition, immunosenescence, and changes in the gut microbiota affect susceptibility to the elderly. Several studies have shown that there is a change in the composition and variability of gut microbiota as we grow older. These changes are considered to increasing the risk of infection and play a role in the pathogenesis of various diseases in elderly. Supplementation of probiotics is expected to overcome the microbiota changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…They manifest their action throughout several physiological (and occasionally pathological) processes, such as tissue remodeling, cancer, injury and aging and function as a cellular defense mechanism to prevent cell damage. Additionally, gut barrier leaks that allow bacteria and/or microbial components to infiltrate may trigger inflammatory reactions [111].…”
Section: Synbioticsmentioning
confidence: 99%
“…They manifest their action throughout several physiological (and occasionally pathological) processes, such as tissue remodeling, cancer, injury and aging and function as a cellular defense mechanism to prevent cell damage. Additionally, gut barrier leaks that allow bacteria and/or microbial components to infiltrate may trigger inflammatory reactions [111].…”
Section: Synbioticsmentioning
confidence: 99%
“…During immunosenescence, a global reduction in the ability to cope with a wide range of stressors occurs, with a concomitant progressive increase toward a pro-inflammatory status, a process that seems to be mediated by the nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B factor; Salminen et al, 2008 ). In addition, inflammatory responses may be caused by the leakage of the intestinal barrier, allowing microbial and/or microbial components to filtrate ( Shalim et al, 2019 ). On the other hand, modifications of the T-cell repertoire have been associated with an increase in morbidity caused by infectious diseases ( Vasto et al, 2006 ), and a low activity of natural killer (NK) cells has been reported as well ( Jing et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%